The Urgency of Contextualizing Islamic Law in Contemporary Society - Khoirudin Yusuf (STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2026)
The contextualization of Islamic law is an approach that emphasizes the importance of understanding social, cultural, and historical contexts in the application of Islamic teachings, particularly normative legal provisions. The urgency of contextualization arises as a response to the complex and diverse dynamics of modern society, where the textual application of Islamic law without considering social realities can lead to inconsistencies and even injustice. This study aims to examine the importance of a contextual approach in the interpretation and implementation of Islamic law, and to illustrate how the fundamental principles of Sharia such as justice (al-adl), public benefit (al-maslahah), and the objectives of Islamic law (maqashid al-shariah) can serve as the foundation for this process. Using a qualitative method and a normative-philosophical approach, this study demonstrates that the contextualization of Islamic law is not a form of deconstruction of religious teachings, but rather an effort to present Islamic law as relevant, adaptive, and solution-oriented in contemporary society. [Kontekstualisasi hukum Islam merupakan suatu pendekatan yang menekankan pentingnya pemahaman terhadap konteks sosial, budaya, dan historis dalam penerapan ajaran Islam, khususnya hukum-hukum yang bersifat normatif. Urgensi kontekstualisasi muncul sebagai respons terhadap dinamika masyarakat modern yang kompleks dan beragam, di mana penerapan hukum Islam secara tekstual tanpa mempertimbangkan realitas sosial dapat menimbulkan ketidaksesuaian, bahkan ketidakadilan. Penelitian ini bertujuan untuk menelaah pentingnya pendekatan kontekstual dalam penafsiran dan implementasi hukum Islam, serta menggambarkan bagaimana prinsip-prinsip dasar syariah seperti keadilan (al-adl), kemaslahatan (al-maslahah), dan tujuan hukum Islam (maqashid al-shariah) dapat dijadikan landasan dalam proses tersebut. Dengan menggunakan metode kualitatif dan pendekatan normatif-filosofis, kajian ini menunjukkan bahwa kontekstualisasi hukum Islam bukan bentuk dekonstruksi ajaran, melainkan upaya untuk menghadirkan hukum Islam yang relevan, adaptif, dan solutif dalam kehidupan masyarakat kontemporer.]